Identification and screening of enzymatic abilities of Ktedonobacteria from forest soil of Cisolok Geothermal Area, Indonesia - MAZYTHA KINANTI RACHMANIA; FITRIA NINGSIH; DHIAN CHITRA AYU FITRIA SARI; YURIZA ESHANANDA; YASUTERU SAKAI; SHUHEI YABE; AKIRA YOKOTA; WELLYZAR SJAMSURIDZAL (Society for Indonesian Biodiversity, 2022)
Abstract. Rachmania MK, Ningsih F, Sari DCAF, Eshananda Y, Sakai Y, Yabe S, Yokota A, Sjamsuridzal W. 2022. Identification and screening of enzymatic abilities of Ktedonobacteria from forest soil of Cisolok Geothermal Area, Indonesia. Biodiversitas 23: 4686-4695. This study aimed to provide information on culturable Ktedonobacteria from forest soil in the Cisolok geothermal area and their potential as enzyme producers. Twelve ktedonobacterial isolates were obtained from this study and identified based on full-sequence of the 16S rRNA gene. Seventeen isolates (including five isolates from previous studies) were used for enzymatic screening and phylogenetic analyses. Screening of amylolytic (0.5% soluble starch) and cellulolytic (0.5% carboxymethylcellulose) (CMC) activities from ktedonobacterial isolates was performed on a ten-fold diluted R2A agar medium, and were incubated at 30 °C for 21 days. The EzBioCloud search revealed that all isolates showed low sequence similarities with Dictyobacter aurantiacus S-27T (97.82 to 98.18%) as their closest related species. The phylogenetic tree showed that all isolates belong to the genus Dictyobacter (family Dictyobacteraceae of the class Ktedonobacteria). All isolates formed a monophyletic group and were placed as the sister clade to D. aurantiacus, as supported by a very strong bootstrap value (99%). Screening of amylolytic and cellulolytic abilities showed that most isolates (88.23%) were able to degrade both 0.5% starch and 0.5% CMC as substrates. This study revealed the presence of Ktedonobacteria with amylolytic and cellulolytic abilities in the forest soil of Cisolok geothermal area.